(untitled) (Conference on English Language Teaching, 2023)
This research describes the ethnosemantic aspect of human attitude/behaviour adjectives in the Banyumasan Javanese to reveal what lexicons are used to describe a person whose attitude/behaviour is regarded good or bad based on the norms in Banyumas society. This research is interesting because in the Banyumasan Javanese such as the Javanese dialect of Yogyakarta or Surakarta, there are many adjectives used to describe human attitudes/behavior. The Banyumasan Javanese has the characteristics of pronunciation which are very loud, strong, and firm. This research is very important to do to explore the lexicon Banyumasan Javanese which can characterize the attitude/behavior of the Banyumas’s people. This research is a descriptive qualitative that aims to reveal language symptoms in society by describing the phenomenon carefully and completely. The data of this research are human attitude/behavior adjectives in Banyumasan Javanese dialect from dictionaries, short stories in Banyumasan Javanese dialect, and Banyumasan Javanese short films.